Penerapan Teknologi WebGL pada Virtual Aquarium Berbasis Tiga Dimensi (3D) - Hendry, Hendry (Jurnal Sistem Komputer, 2011)
Virtual Aquarium is an application which can be used to display an aquarium together with its content that is look like a real one. By using this application, users can see the display of the aquarium like they are looking at the real object because it is displayed in 3D animation. WebGL is one of the technologies that can be used to build this 3D web. It is a canvas context from a HTML element which provides a 3D API graphic object that is implemented into a web browser without using the plug-in. WebGL can provide an interface program for 3D graphic. This new technology use a HTML5 version by accessing the canvas element which then it is accessed by using Document Object Model Interface. As a result, the user can see a Web interface which formerly in 2D, and then it is developed into 3D where the object can be seen from any other sides.